UPAYA GURU BIMBINGAN DAN KONSELING DALAM MENGATASI PERILAKU BULLYING DI MAN LIMA PULUH KOTA - Anita Halima; Hidayani Syam (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study was to find out what efforts were made by Guidance and Counseling teachers in overcoming bullying actions or behaviors that occurred in the Fifty City MAN environment. The background of this research is the increasingly widespread behavior and perpetrators of bullying among students at school. If there is bullying at school, then the school is not a safe and comfortable place for students. Schools that are supposed to be safe places to learn will be made uncomfortable, even frightening environments. Bullying behavior that occurs in this school certainly gets more attention, especially the Guidance and Counseling teachers. With the Guidance and Counseling teacher, of course, this bullying behavior can be overcome so that it does not continue and continues to develop in the school environment, so that the school environment becomes a place that is liked by students.